The Properties of Nitrogen Gas Breakdown Voltage under Direct Current Positive Polarity - Murdiya, Fri; Firdaus; Pardede, Tumpal; Hamdani, Eddy (International Journal of Electrical, Energy and Power System Engineering, 2019)
The type of insulation gases that are usually used in the power circuit breaker (circuit breaker) is the sulfur hexafluoride (SF6) gas, nitrogen (N2) and carbon dioxide (CO2). Most of the electric power systems are using insulating materials such as sulfur hexafluoride (SF6). Sulfur hexafluoride gas (SF6) has a higher dielectric strength than the air. However, Sulfur hexafluoride (SF6) gas is not friendly environmentally and very impact on global warming. The purpose of this study was to test the breakdown voltage of nitrogen gas (N2) (more friendly environmental) as alternative insulation of sulfur hexafluoride (SF6) gas. This study was used sphere and needle electrodes with a distance of 0.5-2 cm and a pressure of 1-4 bar; it was tested for 20 times. From the test results, it obtained that the breakdown voltage of sphere electrodes is more significant than the needle electrodes. Sphere and needle electrodes with a distance of 2 cm and a pressure of 4 bar have a most excellent value of breakdown voltage at the voltage of 140 kV and 79 kV, respectively.